Bibliometric Analysis of Qur’an Reading Through the Tilawati Method in Fluency and Recitation Rhythm Aspects - Aziz Lutfi (PT. Nawa Edukasi Nusantara, 2026)
This study aims to map the development of research on Qur’an reading through the Tilawati method, with specific attention to fluency, recitation rhythm, tajweed, makhraj, and the use of the rost melody. The study addresses the need for a systematic understanding of how the Tilawati method has been positioned in academic literature on Qur’an learning. A bibliometric mapping approach was used by collecting publication metadata from relevant academic databases. The data were selected, cleaned, and analyzed through descriptive bibliometric indicators and VOSviewer visualization, including co-occurrence, overlay, density, and co-authorship analyses. The findings show that the Tilawati method is strongly connected with Qur’an learning, reading ability, tajweed, fluency, students, and reading quality. However, recitation rhythm and the rost melody have not yet become dominant themes, although both are important elements of the Tilawati method. The co-authorship analysis also indicates that author collaboration remains fragmented across small research groups. This study contributes by identifying thematic trends, research gaps, and future directions for Tilawati-based Qur’an learning, especially in relation to rhythm, digital literacy, and reading quality evaluation.